P336 Hypoalbuminemia and oedema in a 4 month-old boy. (June 2019) - O'Sullivan, Deirdre; Koshy, Rincy; Cody, Declan; Bourke, Billy
Abstract : Aims: Primary intestinal lymphangiectasia (PIL) is a well-recognized congenital abnormality of the lymphatic system leading to protein-losing enteropathy (PLE). It is an uncommon disorder seldom seen in clinical practice. The prevalence is unknown. The objective of this case report is to describe the clinical presentation and diagnosis of PIL. Methods: A detailed chart review was performed. Data extracted from the medical records included presenting complaint, disease progression, laboratory results, imaging and clinical measurements. Results: The patient was a 4 month old boy, who presented to the emergency department in Our Lady's Children Hospital, Crumlin (OLCHC) with a 3 week history of bilateral lower limb swelling, easy bruising and a change in stool consistency. The baby was passing watery secretions prior to stool. Stool consistency was clay- like with mucous. Initial bloods showed a severe coagulopathy (PT 204.6 secs, APTT 80.4 secs), severe electrolyte disturbances (Na+128 mmol/l, K+ 2.6 mmol/l), mild transaminase elevation (AST 87 U/l, ALT 49 U/l), metabolic acidosis (pH 7.293, pCO2 4.75, HCO3- 16.9) and profound hypoalbuminemia (13 g/l). The patient was admitted for electrolyte replacement and for further investigation of the underlying cause of the hypoalbuminemia and oedema. Stool alpha- 1-antitrypsin (5.66 mg/g) was markedly elevated confirming protein-losing enteropathy. Further investigations including endoscopic biopsies and allergy testing excluded other enteropathies such as coeliac disease, inflammatory bowel disease, congenital enteropathies and allergic enteritis. As in this case PIL pathology is often mid small bowel and beyond the reach of endoscopic biopsies. Conclusion: Hypoalbuminemia can manifestation from a variety of clinical disorders. This patient had an extensive work-up to exclude other possible causes. Once PLE was confirmed, further investigations were required to identify the underlying cause. The main laboratory findings that supported the diagnosis of PIL included hypoproteinaemia, protein losing enteropathy, lymphopenia, panhypogammaglobulinemia, malabsorption of fat-soluble vitamins and, ultimately, response to a low long chain triglyceride containing diet.